The men who lost Singapore, 1938-1942 - McCrum, Ronald (NUS Press, 2017)
"The British military failure against the Japanese invasion of Singapore in 1942 is a well-documented and closely examined episode. While attention is frequently drawn to the role of the Colonial Governor and his staff during this period, the participation of the civil authorities has not been subjected to the same rigorous scrutiny. In this book, Ronald McCrum undertakes a close examination of the role and the responsibilities of the colonial authorities both in the lead-up to the war and during it. He contends that the colonial government, by pursuing different priorities, needlessly created distraction and confusion. Additionally, the poor, even hostile, relations that developed between the local government and the British military hierarchy impeded a joint approach to the growing threat and affected the course of this campaign. McCrum displays how the tawdry managementof civil defence matters led to unnecessary loss of civilian life."